(untitled) (Agroindustria, Sociedad y Ambiente, 2020)
The use of fossil and hydroelectric energy has led to the deterioration of natural resources due to problems of pollution and deterioration of water basins, which is why clean energy systems such as solar and wind power should be adopted to make sustainable use of these resources in higher education systems where the environmental component is a transversal axis of the curriculum, Awareness of the use of this type of clean energy should be raised. In this regard, the University of the Armed Forces of Ecuador (ESPE) designed and evaluated a prototype wind turbine to provide energy in the areas of internal security, which would serve as a showcase to demonstrate the advantages and applicability of this type of energy in real situations. The aim of the wind turbine prototype was to provide reliable energy to the most remote and vulnerable areas or to systems that need constant energy in case of emergency due to the absence of the conventional distribution network. The results found show that the use of the wind turbine under the climatic conditions of Ecuador for domestic purposes, does not allow substantial energy savings, so it is recommended the construction of wind systems on a larger scale which translates into significant savings in economic terms and reducing the production of CO2, but the low cost of electricity in the region prevents the massification of wind energy systems, despite the environmental advantages and safe use of them, likewise the investment for the implementation and maintenance of wind systems, is expensive when compared with conventional systems.